Ministerial Decree No. 603/2015 amending certain provisions of decree 162/2013 approving recording and classifying the fourth specific branch wells works (4/4) / Translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Serial No. 58/2015